EDUCATIONAL APPLICATIONS IN HIGH SCHOOL FOR THE PREVENTION OF STUDENT CRIMINALIZATION: AN APPROACH FROM RESTORATIVE JUSTICE AND HUMAN RIGHTS - De Mézerville López, Claire (2019)
The following article addresses the intervention from positive discipline as an alternative to common punitive reactions to school misconducts classified as serious and very serious, which advocates a more human approach. It is supported from a human rights perspective based on a restorative justice framework. The article emphasizes the importance of 1) fair processes centered on the student; 2) active student participation in the disciplinary processes, 3) support instead of only sanction towards students with behavior problems and 4) an approach aimed at strengthening the relationships between students with this problem and teachers who prevent or intervene the misconducts. Selected cases from a Costa Rican public school are used to illustrate the benefits of more humanized practices. The article proposes that a restorative approach is not necessarily a substitute for the usual corrective measures, but rather a more effective way to help the people considered perpetrators, assume responsibility for their actions and remain involved in the educational system, instead of isolating them to the point where they get involved in more frequent and severe misconducts.